2008
DOI: 10.1038/onc.2008.203
|View full text |Cite
|
Sign up to set email alerts
|

DAX1, a direct target of EWS/FLI1 oncoprotein, is a principal regulator of cell-cycle progression in Ewing's tumor cells

Abstract: The molecular hallmark of the Ewing's family of tumors is the presence of balanced chromosomal translocations, leading to the formation of chimerical transcription factors (that is, EWS/FLI1) that play a pivotal role in the pathogenesis of Ewing's tumors by deregulating gene expression. We have recently demonstrated that DAX1 (NR0B1), an orphan nuclear receptor that was not previously implicated in cancer, is induced by the EWS/ FLI1 oncoprotein and is highly expressed in Ewing's tumors, suggesting that DAX1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
110
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(115 citation statements)
references
References 39 publications
5
110
0
Order By: Relevance
“…Kinsey et al 30 and Garcia-Aragoncillo et al 40 reported that NR0B1 expression is related to cell proliferative activity in Ewing's sarcoma cell lines. In contrast, the knocked-down expression of NR0B1 did not affect the cell proliferation of A549 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kinsey et al 30 and Garcia-Aragoncillo et al 40 reported that NR0B1 expression is related to cell proliferative activity in Ewing's sarcoma cell lines. In contrast, the knocked-down expression of NR0B1 did not affect the cell proliferation of A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of CpG methylation was inversely correlated with the NR0B1 expression level in clinical samples. Very recently, Garcia-Aragoncillo et al 40 reported that EWS/FLI1 directly binds to the GGAArich region in NR0B1 promoter and transactivates its activity. It is well known that transcription factors may bind to their cognate recognition sequences when the promoter region is relaxed in the unmethylated state.…”
Section: Discussionmentioning
confidence: 99%
“…Among the factors identified (Fig. 2E) that are exclusively associated with Nanog dimers, Nac1, Sall4 and Dax1 are known to enhance proliferation in other cell types (Garcia- Aragoncillo et al, 2008;Ma et al, 2009;Yuri et al, 2009), and we presume that their association with Nanog in ESCs plays a similar role. Interestingly, the WR domain is exclusive to eutherian mammals (see Fig.…”
Section: Nanog Dimers Transform Somatic Cells Promoting Rapid Prolifmentioning
confidence: 99%
“…In Ewing tumors, the EWS/FLI1 oncoprotein directly regulates DAX-1 expression by binding to a polymorphic GGAA-rich region in its promoter [160,161]. Moreover, DAX-1 expression levels in Ewing tumor cell lines correlated positively with the number of GGAA repeats present in their DAX-1 promoter.…”
Section: Ewing Tumors and Other Soft Tissuementioning
confidence: 85%
“…DAX-1 was also reported to physically interact with and modulate the transcriptional activity of the EWS/FLI1 oncoprotein [59]. DAX-1 has an important role in regulating Ewing tumor cells growth since its knockdown blocks cell proliferation in vitro, causing accumulation in the G1 phase of the cell cycle, and significantly impairs the growth of Ewing tumor cells grafted in immunodeficient mice [160]. Importantly, the effect of DAX-1 knockdown on Ewing tumor cells proliferation was observed in the presence of continued expression of the EWS/FLI-1 oncoprotein, indicating the main role of DAX-1 in mediating EWS/FLI1 effects.…”
Section: Ewing Tumors and Other Soft Tissuementioning
confidence: 99%